In vitro and in vivo anticancer effects of two quinoline–platinum(II) complexes on human osteosarcoma models - Ruiz, María Carolina (2019)
Platinum-based drugs, mainly cisplatin, are used for the treatment of several solid tumors such as OS. However, cisplatin treatment often results in the development of chemoresistance, leading therapeutic failure. We have previously reported that platinum complexes containing 8-hydroxyquinoline ligands have good antitumor activity against different cancer cell lines and with a different and better cytotoxic profile than cisplatin. Here, the anticancer properties of two different quinoline–platinum complexes [Pt(Cl)₂(quinoline)(dmso)] (1) [PtCl(8-O-quinoline)(dmso)] (2) on in vitro (2D and 3D) and in vivo models (xenograft tumor of human osteosarcoma in mice) are presented. In this order, [PtCl(8-O-quinoline)(dmso)] (2) impaired cell viability to have a more pronounced antitumor effect than cisplatin on MG-63 osteosarcoma cells (IC₅₀ 4 µM vs. 39 µM). Besides, [PtCl(8-O-quinoline)(dmso)] (2) increased ROS production in a dose-manner response and this compound induced early and late apoptotic fractions of human osteosarcoma cells. Finally, [PtCl(8-O-quinoline)(dmso)] (2) decreased the cell viability of multicellular spheroids and reduced the tumor volume on athymic nude mice N:NIH(S) Fox1nu without inducing side effects. In this way, [PtCl(8-O-quinoline)(dmso)] (2) did not alter the normal cytoarchitecture of liver and kidney and the blood biomarkers (GPT, GOT, uremia, and creatinine) did not suffer modifications. Taken together, our data indicate that these compounds showed a better anticancer performance than cisplatin on in vitro and in vivo studies. These results showed the importance of chelation in the antitumor properties, suggesting that the [PtCl(8-O-quinoline)(dmso)] (2) might be a promising agent for the treatment of human osteosarcoma tumors resistant to cisplatin.